Monitoring and efficiency in governance: a measure for sustainability in the islamic banking industry - Awais, Muhammad; Ullah, Naeem; Sulehri, Numair Ahmad; Mohd Thas Thaker, Mohamed Asmy; Mohsin, Muhammad (Frontiers Media S.A., 2022)
Corporate governance is a set of rules, regulations, procedures, processes, and practices through which an organization is controlled and directed. The present study aimed to examine the monitoring methods used in Islamic banking, including standardized measures for better performance, an individual’s aptitude towards Islamic financial markets, risk propensity, and the level of efficiency of the Islamic banking industry in Pakistan and Malaysia. There is room to improve monitoring systems for Islamic banking operations and standardized measures could improve efficiency, leading to more sustainable performance. The study uses a self-developed semi-structured scale based on literature and expert interviews, after content and context validity to gain a wide range of diverse information. In Pakistan and Malaysia, individuals’ perceptions are different because of differences in the banking environment and preferences. Eventually, the Islamic banking growth rate may differ in Pakistan and Malaysia. Thus, there should be regular monitoring to improve banking performance. Similarly, standardized measures for Islamic banking operations and governance performance in Pakistan and Malaysia will result in more sustainable performance. The antecedents of Islamic corporate governance could be improved to enhance banking performance, which helps individuals make decisions based on available product information. The business growth of the banking industry is based on convenient monitoring policies, standardized performance measures, and, most importantly, excellent corporate governance mechanisms. Improved monitoring measures will further enhance these business operations.